Road Safety Management in Africa: Challenges and Solutions for Tomorrow - (:unkn) unknown (My University, 2023)
With more than 1.3 million people killed and between 20 and 50 million injured in roadcrashes each year worldwide, road safety remains a huge challenge for authorities. Thischallenge is even greater in African contexts. Indeed, a large part of the population has tocirculate in unsafe conditions. The response of the authorities is not straightforward as theeconomic and political situation is not suitable for a road safety policy. Interventions are stillpossible and can be included among the pillars defined by the WHO (infrastructure, users,vehicles, post-crash response and management). Road safety management suggests thatthe public response must be organised, conducted in cooperation with stakeholders. Theresults of the research proposed in this paper show that the situation in this way, althoughdifferent for each country, remains unsatisfactory. There is room for improvement in orderto face the future. They are presented as opportunities to improve the situation.
Keywords: African Research